Jenis-Jenis Jamur Basidiomycetes di Hutan Bukit Beluan Kecamatan Hulu Gurung Kabupaten Kapuas Hulu - Siti Khotimah, Ita Mya Sari, Riza Linda, (Universitas Tanjungpura, 2015)
Basidiomycetes mushrooms are one of the biodiversity in the forest . This study aims to determine a types of Basidiomycetes mushrooms that exist in the Bukit Beluan Forest, Hulu Gurung sub-district, Kapuas Hulu. This research was carried out for 4 months , starting from March 2014 to June 2014 by using Cruise Method. The results showed that the empirically found 32 species of fungi that consists of 4 ordo : Aphyllopholares, Agaricales, Boletales, Tremellales. Furthermore, the results showed that it also found 15 families: Tricholomatacea, Polyporaceae, Ganodermataceae, Boletaceae, Agaricaceae, Tremellaceae, Lentinaceae, Schizophyllaceae, Coprinaceae, Steraceae, Thelephoraceae, Crepidotaceae, Strophariaceae, Lentariaceae, Hydnaceae. The most common fungi derived from the Ordo of Aphyllophorales and Family Tricholomataceae, which are mostly grown on the substrate of dead tree